Self-Regulated Learning In Blended Learning Environment - Jeane Tuilan (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: As technology advances and online learning becomes increasingly prevalent, consideration of students' metacognitive skills grows in importance. This study aims to provide insight into the influence of Self-Regulated Learning (SRL) on the academic outcomes of English students while examining the dominant component within SRL and assessing whether there is a relationship between the use of SRL and gender. Methodology: The research involved 123 students from the English Department of Universitas Negeri Manado (Unima), located in North Sulawesi, Indonesia. An adjusted questionnaire was utilized in a web-based survey to explore the use of SRL amid blended learning settings. Findings: The statistical analysis revealed a positive relationship between SRL and the learning outcomes of the students in the blended learning environment. In particular, students predominantly used achievement orientation as their SRL component in the blended learning environment, while gender differences in the use of SRL strategies were found to be statistically insignificant. Conclusion: As a result, this study highlights the importance of self-regulated learning in the improvement of student outcomes in a blended learning environment. The prominence of performance orientation is a noteworthy aspect of SRL application. Additionally, the lack of notable gender-based disparities in the utilization of SRL implies a level of equality in the educational setting. Originality: This study aims to fill an important gap in current understanding by exploring the complex relationship between SRLs, gender and blended environments among English language learners. By investigating the dynamics of effective learning strategies in the current digital age, this study aims to contribute to a comprehensive understanding of the factors that influence academic success and pave the way for targeted educational interventions.